The components of bid–ask spreads on the London Stock Exchange - Menyah, Kojo; Paudyal, Krishna (Journal of Banking & Finance, 2000)
The objective of this paper is to estimate the cost components of the bid–ask spread on the London Stock Exchange using intraday data. The findings are unambiguous in isolating the three cost components of quoted spreads. They are, therefore, consistent with the earlier work of Stoll based on the quote driven Nasdaq market (Stoll, H., 1989. Journal of Finance 44, 753–776). Additionally, the three spread components vary with the liquidity of the stocks measured by the minimum number of shares market makers are obliged to trade.